Investigation the effect of gamma irradiation on mass preservation of the local mango fruit (chokanan sp.) / Muhammad Yusri Basir and Mohd Zulfadli Adenan - Basir, Muhammad Yusri; Adenan, Mohd Zulfadli (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
At the ambient temperature the mango fruit being a highly perishable fruit possesses very short shelf-life and reaches to respiration peak of ripening process on third or fourth day after harvesting. Due to the overripe of the mango, the mango will lose their mass. The objective of this study was to correlate the percentage of the weight loss of the local mango fruit (chokanan sp.) with different doses of gamma irradiated to the samples. Four groups of mango A, B, C and D were prepared, three groups were irradiated with 400, 800, 1200 Gy according to their groups. Another one group, D is the controlled group. Then, the weights of all groups were measured at initial and final day of the research. Based on the result, there was significant negative correlation between weight loss of the sample at different dose of gamma after 21 days irradiation (p = 0.047, r = -0.953). Thus, gamma irradiation is a potential method to preserve the weight loss of the mango.